Economic burden of road traffic injuries in sub-Saharan Africa: a systematic review of existing literature - Hassan Haghparast-Bidgoli; Justine Davies; Giulia Rinaldi; Marie Hasselberg; Marcella Farrelle Dorothea Ryan-Coker; Dennis H Marke; Marco Necchi (BMJ Open, 2021)
Objective This systematic review aims to explore and synthesise existing literature on the direct and indirect costs from road traffic injuries (RTIs) in sub-Saharan Africa (SSA), the quality of existing evidence, methods used to estimate and report these costs, and the factors that drive the costs.Methodology MEDLINE, SCOPUS, ProQuest Central, Web of Science, Global Index Medicus, Embase, World Bank Group e-Library, Econlit, Google Scholar and WHO webpages were searched for relevant literature. References of selected papers were also examined for related articles. Screening was done following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles were included in this review if they were published by March 2019, written in English, conducted in SSA and reported original findings on the cost of illness or economic burden of RTIs. The results were systematically examined, and the quality assessed by two reviewers using a modified Consolidated Health Economic Evaluation Reporting Standards (CHEERS) checklist.Results Eleven studies met the inclusion criteria. RTIs can cost between INT$119 and 178 634 per injury and INT$486 and 12 845 per hospitalisation. Findings show variability in costing methods and inadequacies in the quality of existing evidence. Prolonged hospital stays, surgical sundries and severity of injury were the most common factors associated with cost.Conclusion While available data are limited, evidence shows that the economic burden of RTIs in SSA is high. Poor quality of existing evidence and heterogeneity in costing methods limit the generalisability of costs reported.